Growth, physiologycal response, yield and phytochemical content of Vernonia amygdalina as affacted by different light intensities, growing media and harvest times - A. Bakar, Nursuhaili; Mohammad Yusoff, Martini; Tengku Muda Mohamed, Mahmud; Misran, Azizah; Ghazemsadeh, Ali; Muharam, Farrah Melissa (Universiti Malaysia Terengganu, 2022)
Vernonia amygdalina Del. is a botanical plant used for self-medication purposes. It is important to understand its acclimatization process, which is influenced by abiotic factors and agronomic practices on growth performance. The present study was conducted to determine the optimum light intensity, growing media, and harvest time required to maximize the growth performance of V. amygdalina. The treatments consisted of three light intensities (30, 50 and 100%), four growing media (soil, cocopeat, empty fruit bunch and burnt paddy husk) and six harvest times. The highest biomass yield of V. amygdalina was achieved with exposure to 50% light intensity. Highest plant height and specific leaf area were found on V. amgdalina grown under 30% light intensity, while 50% light intensity attained the highest photosynthetic rate on empty fruit bunch growing media. Both total phenolic and flavonoid contents of V. amygdalina increased when harvested at 9 and 18 weeks after transplanting. Therefore, the practice of using oil palm empty fruit bunch with 50% of light intensity exposure and harvest at 18 weeks after transplanting is recommended to optimize the growth and phytochemicals yield of V. amygdalina.